Data integration in the life sciences : 13th International Conference, DILS 2018, Hannover, Germany, November 20-21, 2018, Proceedings /: 13th International Conference, DILS 2018, Hannover, Germany, November 20-21, 2018, Proceedings. (2019) - Unknown
No abstract available